“Come and See” in the Age of Algorithms : Reconfiguring the Johannine Pedagogical Triangle in the Face of Artificial Intelligence - Nomenjanahary Jenny Patrick; Robijaona Rahelivololoniaina Baholy (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2026)
The rapid integration of generative Artificial Intelligence (AI) into educational institutions introduces profound anthropological, sociological, and theological challenges to traditional formative practices. This study establishes a rigorous interdisciplinary critique of Large Language Models (LLMs) by contrasting modern computational operations with the ancient relational structures found in the first-century Mediterranean world. Utilizing a qualitative, socio-historical, and exegetical methodology anchored in the discipleship recruitment narrative of John 1 :35–51, this research systematically retrieves three foundational Johannine concepts: akoloutheō (existential rupture), menō (intimate, temporal dwelling), and horaō (progressive spiritual vision). These philological elements, contextualized through ancient honor/shame dynamics and social memory theory, are mapped onto Jean Houssaye’s classical pedagogical triangle to diagnose the structural disruptions caused by digital acceleration. The findings reveal a fundamental ontological incompatibility between the relational requirements of authentic human formation and the transactional efficiency of predictive computing. While AI functions effectively as an "exegetical orthosis" (a supportive auxiliary tool for data aggregation and linguistic refinement), its total substitution as a pedagogical prosthesis destroys the educator’s testimonial authority (martyria) and short-circuits the learner’s necessary internal "struggle with the text." Consequently, this article proposes an innovative normative framework termed a "pedagogy of augmented dwelling." Articulated through six operational guiding principles—including the primacy of personal study, the closed-loop rule, and the absolute unavailability of the internal forum—this model successfully domesticates algorithmic tools. Ultimately, this research demonstrates that the Christological invitation to "come and see" cannot be reduced to automated prompt-response mechanics, but imperatively demands physical presence, temporal duration, and lived, incarnate encounter.